COURSEWARE FOR VISUALLY IMPAIRED CHILDREN' - Norehsan, Nurul Alia (Universiti Teknologi Petronas, 2005)
'Courseware for Visually Impaired Children' is developed to help the blinds for their education learning process. This courseware is focusing for children from 7-10 years old. The objective is to develop a courseware that satisfies MAB (Malaysian Association for the Blind) to assist requirements blind children in their learning education. This courseware is developed because there is lack of teaching materials and experts to assist blind children in their education. Currently, teachings are based on communication between the teacher and the blind children. The problem with the current learning materials is there is no electronic media being used to ensure the efficiency and effectiveness of teaching methods. This courseware will enable theblind children to have their chance in using computer and learn how to read word, learn alphabetical, typing and memorizing numbers. They are exposed to new software that needs them to navigate this software using computer by using only keystroke and no mouse pointing. Based on interview, this courseware is useful for MAB in enhancing their ability and efficiency in delivering learning to blind children. The methodology selected for this courseware are based on five phases that are; project planning, system analysis, system design, coding and testing and project presentation. The expected output for this courseware will be the implementations of a real computerize system that can be used by the teachers to assist the blind children in their education.